Assesment of the Candidate Suppliers’ Fluency in ISO GPS Standards Essential Principles, Rules and Indications - Marcin Błaszczyk; Zbigniew Humienny (Journal of Machine Engineering)
Many potential suppliers state that they are ready to produce components according to specified requirements as they are familiar with the ISO GPS system for geometrical tolerancing. In many instances, this is not true. This paper discusses a survey developed to assess the geometrical tolerancing skills and results derived from this survey executed among 15 potential suppliers. The investigation aims to preselect potential suppliers and evaluate how much support they will require, while also evaluating the risks associated with placing an order with a particular supplier. The survey is based on the online test comprised of 27 closed-end questions used to identify strengths and weaknesses of a candidate supplier’s personnel. Most of the questions include drawings with indicated tolerance and drawings of the possible parts with exaggerated deviations. The main conclusion is that most responders disclose a low level of understanding of the ISO GPS system. Urgent education is needed.